Environmental changes and their effects on carbon isotope distribution in Lake Plateliai over the past 130 years: insights from sediment organic fractions and diatom assemblages - Rūta Barisevičiūtė; Jūratė Karosienė; Jūratė Kasperovičienė; Ričardas Paškauskas; Olga Jefanova; Piotr Szwarczewski; Žilvinas Ežerinskis; Laurynas Butkus; Justina Šapolaitė; Jonas Mažeika (PLoS ONE, 2026)
In this study, we investigated how anthropogenic activities have affected the carbon cycle and biological productivity in a mesotrophic lake over the past 130 years. We analysed the carbon isotope distribution in two organic sediment fractions: alkali-soluble and alkali-insoluble along with diatoms and the organic matter content in the sediments. Over the course of 130 years, the freshwater reservoir age (RA) in both organic sediment fractions in this ecosystem changed by 872.4 ± 80.2 y. In this lake ecosystem, the values of specific radiocarbon ( 14 C) activity in both sediment fractions remained very similar during the periods when the water level was kept more or less constant (1885–1932 and after 1985) and varied in the range of 1 pMC. Any changes in the plankton community affecting the ratio of stable carbon isotopes in the alkali-soluble fraction had no effect on the redistribution of 14 C between the two organic sediment fractions. The differences in the RA up to 352.7 ± 57.4 y observed between the fractions during the Second World War and between 1960 and 1976 were associated with changes in the water level and the input of allochthonous substances into the lake ecosystem.